The Ideational, Interpersonal and Textual Meaning in Jokowi Dodo's Inauguration Speech - Samsudin, Samsudin (e-Journal of Linguistics, 2019)
Systemic Functional Linguistic offers a model of approach in analyzing discourse concerning to reveal how language is used to negotiated meaning. Research paper, also known as research article presents Jokowi Dodo’s Inauguration speech in terms of Ideational, interpersonal and textual meaning. Therefore, this study aimed to explain the realization of Ideational, Interpersonal and Textual Meaning in Inauguration speech. Descriptive qualitative  Research design was used in this study with one Jokowi Dodo’s text speech taken as the subject of analysis . The findings revealed that the meanings were realized by the president’s  language choice. Ideational meaning realized in research paper showed that the president presented his future dreams in state of doing through relational process and material process with help of other process types. However, Interpersonal meaning realized in the research paper showed that the research paper was carrying the speech role as giving information. Textual meaning was realized through the use of the speech opening and giving appreciate to participants who attended in  Inauguration speech and also hopes to all participants. The realization of the meaning also could give benefit to participant and researcher in having guideline when they are giving speech in public area.